Attachment and spiritual coping in patients with chronic schizophrenia - Rieben, Isabelle (Mental health, religion & culture, 2014)
Many studies on spirituality in psychosis have shown that, compared to a nonclinical population, patients make more use of spiritual beliefs/religious practices to deal with their problems. Our research question was to test whether attachment to spiritual figures could be a good explanation for religious coping strategies in patients with psychosis. First, adult attachment was investigated in 28 patients with chronic psychosis and 18 controls, using the Adult Attachment Interview. Diagnostic evaluations were performed with the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders (4th edition, Text Revision) Axis I disorders and symptomatic evaluation with the Brief Psychiatric Rating Scale. Results also show a high prevalence of insecure avoidant attachment in patients, and suggest that a significant part of religious coping might be explained by the theory of attachment (64% of the patients, 78% of controls). The implications of these results are interpreted in light of correspondence and compensation hypotheses.